The Intention To Blow The Whistle : Testing The Correlation Between Ethical Leadership And Retaliation In The Organization - Fatchan, Ilham Nuryana; Alfalisyado, Alfalisyado; Randikaparsa, Irawan; Fatchan, Fuad Hudaya (Integrated Journal of Business and Economics (IJBE), 2024)
This research helps explain the factors that influence a person's intention to do whistleblowing. This study examines the effect of retaliation (the treatment of revenge) and ethical leadership on the whistleblowing decisions of postgraduate students with masters of accounting at universities in Central Java. The novelty of our study is First, we fill in gaps in previous studies using students as the population; most studies use employees (such as auditors) as the main population.This study is considered to be the first micro-level analytical research in the area. Second, answering whether the ethical principles possessed by superiors influence employees to do whistleblowing. Questionnaires were administered privately, and respondents were convinced of retaliation, value orientation and whistleblowing intentions for data confidentiality and the anonymity of the respondent's identity. Testing the data in the study used the Partial Least Square (PLS) analysis tool.The primary research data used in the research were obtained through questionnaires. The results of the study show that: (1) Ethical Leadership has a positive and significant effect on the intention to do whistleblowing; (2) Retaliation or the threat of retaliation has a negative and significant effect on a person's intention to carry out a whistleblowing.